Analysis of Location Errors of the U.S. National Lightning Detection Network Using Lightning Strikes to Towers. Issue 9 (8th May 2020) - Zhu, Yanan; Lyu, Weitao; Cramer, John; Rakov, Vladimir; Bitzer, Phillip; Ding, Ziqin
Abstract: The location accuracy of the U.S. National Lightning Detection Network (NLDN) has been evaluated using as ground‐truth rocket‐triggered lightning data or video records but only at a few specific locations. In this study, by using the NLDN data for the events attributable to lightning strikes to towers, the location error of the NLDN across the entire contiguous United States was evaluated for the first time. We found that, on average, the NLDN median location error reduced from 198 to 84 m after the 2013 NLDN upgrade. The location error at the periphery of the network is significantly larger than that in its interior. In the coastal regions, there is directional location bias toward the water. Simulation results suggest that the bias is related to the lengthening of field waveform front due to electromagnetic wave propagation over lossy ground coupled with the asymmetrical sensor configuration relative to the strike point (lack of offshore sensors). Key Points: NLDN location errors were estimated for CONUS using NLDN‐reported events that can be reasonably attributed to lightning strikes to towers After the 2013 upgrade, the median location error averaged over the interior of the network is 75 m versus 158 m for its periphery The directional location bias in coastal regions is related to propagation effects coupled with the lack of sensors over water